Incivility and the effect on the learning environment within operating rooms - Duchscher, Chelsea (Operating Room Nurses Association of Canada Journal, 2026)
Incivility in the operating room (OR) is well documented, yet its effect on learning remains unclear. This narrative review explores how perioperative learners, including nursing, medical, anesthesia, and surgical technology students, experience incivility during OR clinical practicums and how it shapes the learning environment. Fourteen studies published from 2018–2025 were analyzed. Findings indicate that incivility contributes to anxiety, avoidance behaviours, reduced engagement, and weakened professional identity. The OR learning environment is further influenced by instructor support, the high-stress, high-risk nature of the setting, and the established OR culture. Gaps include the need for discipline-specific research, Canadian studies, and comparisons across healthcare systems. This study advocates for establishing a safe and supportive learning environment for learners in perioperative clinical practicums. This includes having consistent, supportive instructors; preparing students for the stressful operating room environment with timed simulations, cognitive rehearsals, and stress management training; and preventing the normalization and recurring cycle of incivility through clear policies and accessible reporting systems.